A PSICOPEDAGOGIA SERIA UMA POSSIBILIDADE PARA O ENFRENTAMENTO DAS DIFICULDADES DE APRENDIZAGEM? - Araujo, Paula Fernandes Corrêa de (2014)
The practice of the teacher in the classroom has great importance for a successful development of the student. In primary education we can notice high numbers of children with learning disabilities related to reading and writing - they know how to read what is written, but they cannot interpret what they are reading. In this context, this study aimed to conduct a discussion to see if, indeed, the psycho-pedagogical acquirements are facilitators for organizing interventions in pedagogical practice of teachers who face learning difficulties of students in reading and writing process, and to investigate whether teachers who have the psycho-pedagogical knowledge are more successful in terms of satisfactory results considering the interventions with their students, then to teachers who have no such knowledge. This study is delimited in the scope of the elementary school, and had as subjects, six pedagogue teachers who work or worked in the 3rd or 4th year of Cycle I (the first series) in public schools at São Paulo - three of them have the psychopedagogy course and three of them do not have the psychopedagogy course, and it had as motivating the following questions: A psychoeducational practice can contribute positively in the school context? The pedagogue teacher, with psycho-pedagogical knowledge, feels it is easier to deal with learning difficulties? It is also conducted a historic recovery about the Psychoeducation emergence in Brazil and its field performance, as well as reflections on the discussion about the difficulties of learning is related to the difficulties of teaching and learning. The basic academic references, for deepening discussions of some proposals, was based on authors such as Bossa, 2011; Fernández, 1991; Pain, 1992; Polity, 2002 and Franco, 2003. To collect data from selected subjects, we conducted semi-structured interviews, which were audio-recorded and transcribed for later analysis categories organization, through the methodology of content analysis proposed by Franco (2003). Through this study we found that as the psychopedagogy has an interdisciplinary feature, much of its theoretical and practical contributions come from other areas of knowledge, such as pedagogy. Thus, much of interventional practices of teachers with psychopedagogy to students who face learning difficulties in reading and writing, are the same as the teachers without psychopedagogy, use in the classroom.